Influence of maggot mass temperature in the development of chrysomya megacephala in estimating post mortem interval (PMI) in Kelantan,Malaysia. - Azlan, Nurhazirah Zainul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
The major contribution of forensic entomology is in the estimation of postmortem interval (PMI). Postmortem interval is the time elapsed since death, which can be used for narrowing down the suspect's presence at the time the body was disposed thereby linking the suspect with the crime. Determination of the PMI is based on two principles, one by studying the life cycle of a specific species of insect and the other by studying the succession of different species of insects. As a poikilothermic (cold-blooded) organism, rate of growth of the larvae is a function of temperature and time. In this research, the influence of maggot mass temperature is evaluated as a factor affecting the rate of growth of the larvae. Maggot mass is referred to larvae that grow in groups. The larvae when in a mass produce heat that can be higher than the ambient temperature. In temperate countries, higher maggot mass temperature can sustain continual growth despite low ambient temperature. The range of variation between ambient temperature and maggot mass temperature in temperate countries has been reported to be 17°C to 33°C. Due to the higher maggot mass temperature, life cycle of insect is completed earlier. Research on the influence of maggot mass temperature on development of dipteran flies in tropical countries like Malaysia is lacking. This research conducted at Universiti Sains Malaysia in Kelantan, Malaysia, a tropical environment evaluated the influence of maggot mass temperature in the development of Chrysomya megacephala in estimating the PMI in Kelantan, Malaysia. C. megacephala is chosen as it is the most prevalent fly of forensic importance in Malaysia. The experiments were designed to cover both sunlit habitat and shaded habitat. The development of maggots in mass was studied in relation to the development of scarce maggots in the same environment. The animal model decomposed was beef meat and as it was covered using a slotted plastic basket, the temperature inside the basket was considered the ambient temperature and five replicates of the experiment were carried out. The results indicated that the difference in the mean maggot mass temperature ranged from -0.1 to 6.9 °C when compared to the basket temperature. The time taken for the larvae to attain the three instars which are the first, second and third was formal to be similar irrespective of whether they are in a mass or are sparse. However, the maggots in mass were always longer than there in sparse. The results indicate that maggot mean temperature has to be taken into consideration while estimating PMI.